Case Studies: Its Impact on Learning and Research - Pratap Lingam, P. (Journal of Information and Knowledge, 1980)
Discusses the role of case studies in the development of a subject and in the teaching and learning of skills; discusses Walton, Khare and Popper models to identify the value of case studies in research and learning. Suggests that case study method should be employed in teaching of library and information science. Suggests that practising libraries should write record cases in reference and information services.